The wolf of Wall Street - Scorsese, Martin; Winter, Terence; DiCaprio, Leonardo; Aziz, Riza; McFarland, Joey; Koskoff, Emma Tillinger; Hill, Jonah, 1983-; Robbie, Margot; McConaughey, Matthew, 1969-; Chandler, Kyle; Reiner, Rob; Favreau, Jon; et al. (Hollywood, California : Paramount Pictures, 2014)
Sex. Money. Power. Drugs. Brace yourself for an outrageous true story from legendary filmmaker Martin Scorsese. Jordan Belfort, a young stockbroker, is hungry for fame and glory in New York City, where corruption is king and more is never enough.
DVD, NTSC region 1, widescreen presentation enhanced for 16:9 TVs; 5.1 Dolby Digital.
In English, dubbed Spanish, or dubbed French; English, French or Spanish subtitles; closed-captioned; English audio description track for people with visual disabilities.
Title from disc surface.
Leonardo DiCaprio, Jonah Hill, Margot Robbie, Matthew McConaughey, Kyle Chandler, Rob Reiner, Jon Favreau, Jean Dujardin, Joanna Lumley, Christine Ebersole, Jon Bernthal, Shea Whigham.
Costume designer, Sandy Powell ; editor, Themla Schoonmaker ; production designer, Bob Shaw ; director of photography, Rodrigo Prieto.
Based on the book by Jordan Belfort.
Keywords: Belfort, Jordan -- Drama; Stockbrokers -- New York (State) -- New York -- Drama; Securities industry -- New York (State) -- New York -- Drama; Wall Street (New York, N.Y.) -- Drama; Success -- New York (State) -- New York -- Drama; Nineteen eighties -- Drama; Nineteen nineties -- Drama; Feature films; Fiction films; Biographical films; Film adaptations; Video recordings for the hearing impaired; Video recordings for people with visual disabilities